Cancer Risk Assessment From Multi-Exposure to Chloroform in Drinking Water of Ilam City, Iran - Kamyar Arman; Ali Reza Pardakhti; Noushin Osoleddini; Mostafa Leili (Hamadan University of Medical Sciences, 2016)
Among various trihalomethane (THM) compounds, chloroform is considered to be the main compound and was selected as an indicator of THMs in this study. This study aims to calculate and assess the lifetime cancer risks resulting from chloroform intakes of various exposure routes in Ilam's urban drinking water. The samples were analyzed using a gas chromatograph equipped with a flame ionization detector (GC/FID). The results showed that average chloroform concentrations in different districts were between 20 and 30.3 μg/L, and the highest concentrations were detected in district 4 with a value of 32.2 μg/L. All water samples contained concentrations of chloroform below the standards of the world health organization (WHO) and the institute of standards and industrial research of Iran (ISIRI). Assessment of lifetime cancer risks was carried out using prediction models for different exposure routes, including ingestion, inhalation, and dermal routes for people living in Ilam city. The highest risk from chloroform seems to be from the oral ingestion route, followed by inhalation and dermal absorption. The maximum and minimum lifetime cancer risks were 6.59 × 10 - 6 and 5.95 × 10 - 6 in districts 4 and 3, respectively. It was also concluded that the average lifetime cancer risk was 6.26 × 10 - 6 in all districts. Based on the population data, the total number of expected lifetime cancer cases from exposure to chloroform is 1 for Ilam city.